2016
DOI: 10.3892/ol.2016.5284
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of forbesione isolated from Garcinia hanburyi on cholangiocarcinoma in vitro and in vivo

Abstract: Abstract. Cholangiocarcinoma (CCA) is a malignancy with no effective therapy and poor prognosis. Forbesione, a caged xanthone isolated from Garcinia hanburyi, has been reported to inhibit proliferation and to induce apoptosis in human CCA cell lines. The present study aimed to further explore the potential anticancer properties of forbesione by testing its effects against the hamster CCA cell line Ham-1 in vitro and in vivo. It was observed that forbesione inhibited the growth of Ham-1 cells in vitro and suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…In addition, it was found that the expression of p27 and p21 was increased, which may describe why proliferating bile duct cell markers and cell nuclear antigen in forbesone-treated Ham-1 cells in vitro and in forbesone-treated hamster tumor tissues Cytokeratin 19 are reduced. In addition, forbesione promotes apoptosis through a variety of mechanisms [ 79 ]. Increased expression of Fas, Fas-related death domains, and activated caspase-3, as well as decreased expression of procaspase-3 and 8, activates the death receptor pathway [ 79 , 80 ].…”
Section: Major Medicinal Plants With Anticancer Activities and Possib...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it was found that the expression of p27 and p21 was increased, which may describe why proliferating bile duct cell markers and cell nuclear antigen in forbesone-treated Ham-1 cells in vitro and in forbesone-treated hamster tumor tissues Cytokeratin 19 are reduced. In addition, forbesione promotes apoptosis through a variety of mechanisms [ 79 ]. Increased expression of Fas, Fas-related death domains, and activated caspase-3, as well as decreased expression of procaspase-3 and 8, activates the death receptor pathway [ 79 , 80 ].…”
Section: Major Medicinal Plants With Anticancer Activities and Possib...mentioning
confidence: 99%
“…In addition, forbesione promotes apoptosis through a variety of mechanisms [ 79 ]. Increased expression of Fas, Fas-related death domains, and activated caspase-3, as well as decreased expression of procaspase-3 and 8, activates the death receptor pathway [ 79 , 80 ]. Increased expression of activated caspase-9, B-cell lymphoma- (Bcl-) 2-like protein 4 and B-inhibitors, expression of Bcl-2, survivin, procaspase-9, and nuclear factor-B decreased p65, driving mitochondria way [ 80 ].…”
Section: Major Medicinal Plants With Anticancer Activities and Possib...mentioning
confidence: 99%
See 1 more Smart Citation
“…The biological activities and mechanisms of action of isomorellin (101) and forbesione (103) against cholangiocarcinoma has been a major research area for Reutrakul's research team since 2010 (Figure 8) [140][141][142][143][144]. Four caged xanthones, gambogic acid, 101, isomorellinol (102) and 103, have been tested against two cholangiocarcinoma cell lines, KKU-100 and KKU-M156 [140].…”
Section: Isomorellin and Forbesionementioning
confidence: 99%
“…Forbesione has been demonstrated to inhibit the growth of the Ham-1 hamster cholangiocarcinoma cell line and Ham-1 allografts in a hamster model, with no observed in vivo toxicity or adverse effects [144]. This compound arrests the cell cycle at S phase through decreasing the protein expression of cyclin A, cyclin E and Cdk2, as well as promoting the upregulation of p21 and p27.…”
Section: Isomorellin and Forbesionementioning
confidence: 99%